Aspectos ambientales y de manejo que determinan el crecimiento del kikuyo (Cenchrus clandestinus Hochst. ex Chiov. Morrone) en la Provincia de Ubaté (2019)
This research had two main objectives, to characterize the growth of the kikuyo grass in the province of Ubaté according to the altitude, environmental factors and soil characteristics and to determine the optimum harvest time of the kikuyo according to the leaf stage and nitrogen fertilization. Three experiments were carried out. In the first, plots of 100 m2 were established in 9 farms located at different altitudes. Each plot was divided into 6 sub-plots in which cuts were made at 15, 30, 45, 60, 75 and 90 days. A multiple linear regression analysis was carried out to determine the variables that most influenced dry matter production (DM), undisturbed height (UH) and leaf area index (LAI). At higher altitude (lower temperature), the kikuyo loses ability to compete with other species and the plots become polyphytic. Growth rates were higher in kikuyo grasslands (60 kg DM ha-1) than in polyphytic grasslands (30 kg DM ha-1). Precipitation increases DM yield, LAI and UH. There was no effect of the variables associated with the soil included in the model (pH and CIC). In the second experiment 3 plots of 1m2 were established in three farms located at different altitudes, in which kikuyo stolons were marked to measure the leaf appearance rate and determine the base temperature for growth (bT) by the least coefficient of variation method. The bT was 4 °C and the thermal time for the appearance of the first leaf (97.5 GDD) was higher than for the second (74.2 GDD), third (73.8 GDC) and fourth leaf (76.0 GDD), aspect related to the mobilization of reserve carbohydrates for regrowth. The third experiment was carried out in pots under greenhouse. Four nitrogen levels (0, 50, 100 and 150 kg N ha-1 year-1 and four leaf stages (3, 4, 5 and 6 leaves per stolon) were evaluated in a completely randomized design with a factorial arrangement 4*4. The nutritional quality was better in the stage 3 to 4 leaves and the DM production was higher in 5 and 6 leaves (p<0,05). Nitrogen fertilization increases UH, density of stolons, production of DM from leaves, stems and green forage, the ratio of green forage: dead forage and nutritional quality (higher CP contents and lower contents of NDF) (p<0,05). Without fertilization and little N available in the soil, it is difficult to reach the biomass recommended for grazing (2,500 kg DM ha-1) at 6 leaf stage. With 100 kg N ha-1 It is possible to harvest at 5 leaf stage and above this level of fertilization, it is possible to harvest in the stages of 3 to 4 leaves.